2005
DOI: 10.1590/s1415-54192005000400009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos sinais de DTM em pacientes ortodônticos assintomáticos

Abstract: O objetivo deste trabalho foi estudar a presença de sinais de disfunção têmporo-mandibular em pacientes assintomáticos ao início, durante e após o tratamento ortodôntico, através de uma revisão da literatura, verificando se o exame clínico é um método suficiente para diagnóstico, e se o tratamento ortodôntico é fator contribuinte para o desenvolvimento dessas disfunções têmporo-mandibulares nestes pacientes. O tratamento ortodôntico não pode ser considerado fator contribuinte para desenvolvimento de disfunções… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(54 reference statements)
1
3
0
5
Order By: Relevance
“…Regarding the questionnaire, it is noticed that about 70 to 80% of TMD patients showed positive responses to TMJ sounds, muscle discomfort or pain while chewing, headaches and pain in the cervical region, agreeing with work related to the main signals and symptoms of patients with TMD. 7,11,20 Signs and symptoms of TMD can occur in healthy people 2,14 as found in the control group in this study, that despite the classification as "absent" by Fonseca et al 4 index, it is observed the presence mainly of headache (10%) and joint noise (10%). The TMJ joint noises are frequent, even in an asymptomatic population, while the absence of joint noise cannot be used as a rule for articulation normality.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Regarding the questionnaire, it is noticed that about 70 to 80% of TMD patients showed positive responses to TMJ sounds, muscle discomfort or pain while chewing, headaches and pain in the cervical region, agreeing with work related to the main signals and symptoms of patients with TMD. 7,11,20 Signs and symptoms of TMD can occur in healthy people 2,14 as found in the control group in this study, that despite the classification as "absent" by Fonseca et al 4 index, it is observed the presence mainly of headache (10%) and joint noise (10%). The TMJ joint noises are frequent, even in an asymptomatic population, while the absence of joint noise cannot be used as a rule for articulation normality.…”
Section: Discussionsupporting
confidence: 46%
“…The TMJ joint noises are frequent, even in an asymptomatic population, while the absence of joint noise cannot be used as a rule for articulation normality. 2,7,14 One must perform a careful clinical examination of signs and symptoms of TMD, before starting the orthodontic treatment, for the patient to be alerted in case of presence of these signs and / or symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O estalo pode ou não ser acompanhado de dor 12 e o estalido (clicking) duplo, na abertura e fechamento mandibular, caracteriza-se por deslocamento do disco articular com redução, e a articulação silenciosa assintomática e limitação na abertura indicam deslocamento do disco articular sem redução. A crepitação freqüentemente indica uma artrose 10 .…”
Section: Conflito De Interesses: Inexistenteunclassified
“…Estás articulações apresentam uma series de características especificas, as quais dificultam a ocorrência de deslocamento do disco articular, dentre essas estão: sua forma anatômica, a existência da pressão intra-articular a qual é tida como um dos principais fatores responsáveis pela estabilidade desta articulação, o fato de serem sustentada pela constante atividade muscular e dos ligamentos os quais limitam os movimentos destas (Pinheiroet al, 2010;Delboni & Abrão, 2005). O fato de as superfícies destas articulações serem revestidas por tecido conjuntivo denso fibrosos (fibrocartilagem) e não de cartilagem hialina da mesma maneira que ocorre em outras articulações do corpo, proporciona um melhor sistema de reparação e regeneração (Pinheiroet al, 2010;Delboni & Abrão, 2005).…”
Section: Revisão Da Literaturaunclassified